Method for detecting electrical transport characteristics and structure of two-dimensional chalcogenide under high voltage
Patent Information
- Application Number
- CN202410508417.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-25
- Publication Date
- 2025-01-07
AI Technical Summary
但是,唯一美中不足的是本征石墨烯禁带宽度为零,大大阻碍了石墨烯在场效应晶体管中的应用
[0005] In view of the above-mentioned shortcomings of the existing technology, the purpose of the present invention is to provide a method for electrical transport characteristics and structure detection of two-dimensional chalcogen compounds under high pressure. The present invention uses a solid-phase reaction method to explore WS 2-x Se 2 Polycrystalline growth conditions, successful preparation of pure WS 2-x Se 2 Polycrystalline samples, study their magnetic transport properties, and prepare WS 2-x Se 2 Polycrystalline, study of electrical transport properties, WS 2 - x Se 2 The influence of polycrystalline temperature-resistance and magnetic field-resistance effects under high pressure provides a detailed reference experimental method for detecting the electrical transport properties of two-dimensional chalcogenides. At the same time, by using XRD on the prepared powder and bulk materials Characterize detection technology, compare the position and height of the three strongest diffraction peaks, field emission scanning electron microscopy, transmission electron microscopy, electron backscatter diffraction and electron probe technology to determine the phases contained in the material and the corresponding crystal structure. And detect and prepare WS 2-x Se 2 The characterization of the distribution of the second phase of polycrystalline samples provides a detailed reference experimental method for the detection of two-dimensional chalcogen compound structures.
Smart Images

Figure CN119269581A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of two-dimensional materials, and in particular to a method for detecting the electrical transport properties of two-dimensional chalcogenide compounds under high pressure. Background Art
[0002] Two-dimensional materials refer to new materials that can exist independently of single atoms or less atomic layers, which are mainly formed by covalent bonds. Due to the introduction of quantum confinement effects due to the reduction of material dimensions, two-dimensional materials exhibit novel physical, electronic and chemical properties. The star material graphene has many excellent properties such as ultra-high room temperature carrier mobility, extremely high specific surface area, and room temperature quantum Hall effect, which makes graphene have unlimited application possibilities in electronics, optical devices and sensors. However, the only drawback is that the intrinsic graphene bandgap is zero, which greatly hinders the application of graphene in field effect transistors. Most TMDs materials have a bandgap of 1 to 2 eV, which makes up for the shortcomings of graphene.
[0003] Therefore, TMDs materials are another new type of two-dimensional materials that have attracted much attention after graphene. TMDs are typical two-dimensional layered structure materials, and one type of two-dimensional chalcogenides has attracted widespread attention in the academic community due to their large unsaturated magnetoresistance effect. Two-dimensional chalcogenides have a layered structure, with van der Waals gaps between adjacent layers and a large specific surface area, which makes them have broad prospects in capacitive energy storage and sensing applications. Sensors based on two-dimensional chalcogenides have a large surface area to volume ratio, higher sensitivity, more selectivity and lower power consumption.
[0004] In summary, developing a method for detecting the electrical transport properties and structure of two-dimensional chalcogenides under high pressure is still a key issue that needs to be urgently addressed in the field of two-dimensional material technology. Summary of the invention
[0005] In view of the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a method for detecting the electrical transport properties and structure of two-dimensional chalcogenides under high pressure. The present invention uses a solid phase reaction method to explore the 2-x Growth conditions of Se2 polycrystals, successful preparation of pure WS 2-x Se2 polycrystalline samples, study its magnetic transport properties, prepare WS 2-x Se2 polycrystal, study its electrical transport properties, WS2- xThe influence of temperature-resistance and magnetic field-resistance effect of Se2 polycrystal under high pressure provides a detailed reference experimental method for the detection of electrical transport properties of two-dimensional chalcogenide compounds. At the same time, by using XRD characterization detection technology, comparing the position and height of the three strong diffraction peaks, field emission scanning electron microscopy, transmission electron microscopy, electron backscatter diffraction and electron probe technology to characterize the prepared powder and bulk materials, the phases contained in the material and the corresponding crystal structure are determined, and the prepared WS is detected. 2-x The characterization of the distribution of the second phase of Se2 polycrystalline samples provides a detailed reference experimental method for the detection of two-dimensional chalcogenide compound structures.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for detecting the electrical transport properties of two-dimensional chalcogenide compounds under high pressure, comprising:
[0008] S1. Preparation of WS by solid phase reaction method 2-x Se2 polycrystalline samples, where X = 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1;
[0009] S2, prepare the WS 2-x Se2 polycrystalline samples were sliced into rectangular thin slices;
[0010] S3, the WS is measured by the four-electrode method 2-x The resistivity curve of Se2 polycrystalline sample under zero field with temperature, the temperature T ranges from 5K to 300K;
[0011] S4. The WS was tested at different temperatures of T = 5K, 50K, 100K, 200K, and 300K using the four-electrode method. 2-x The resistivity of Se2 polycrystalline samples varies with magnetic field, and the magnetic field range is 0 to 5 T;
[0012] S5. Calculate the WS using the formula MR = [(ρ(H) - ρ(OT))] / p(H) × 100% 2-x The magnetoresistance value of Se2 polycrystalline sample is obtained by 2-x The curve of magnetoresistance variation with magnetic field of Se2 polycrystalline sample.
[0013] The present invention is further configured as follows: in step S1, WS is prepared 2-x The steps for Se2 polycrystalline sample are:
[0014] S10, according to 1 ∶ 1 ∶ Weigh high purity W, S, and Se powders at a weight ratio of 2;
[0015] S11. Put the weighed high-purity W, S, and Se powders into a mortar, add alcohol and grind, and heat at 55-85°C until the alcohol is completely evaporated;
[0016] S12, loading the uniformly mixed high-purity W, S, and Se powders into an Al2O3 crucible, and then placing the crucible into a quartz tube, and using a vacuum tube sealing device to evacuate and seal the quartz tube;
[0017] S13, placing the sealed quartz tube into a box furnace, keeping it at 650-750°C for 12-14 hours, and then naturally cooling it down to 20-25°C;
[0018] S14. Take out the sample, grind it again, press it into tablets, seal the tube, put it into a high-temperature chamber furnace and sinter it at 750-850°C. Keep it warm for 12-14 hours, then naturally cool it down to 20-25°C and take it out.
[0019] The present invention is further configured as follows: in steps S3 and S4, when the four-electrode method is used for detection, the resistivity difference is calculated using the temperature difference electromotive force generated by the upper and lower electrodes, and the protective gas is helium.
[0020] A method for detecting the structure of a two-dimensional chalcogenide compound under high pressure comprises the following steps:
[0021] S1. Preparation of WS by solid phase reaction method 2-x Se2 polycrystalline powder and bulk samples;
[0022] S2. Perform XRD characterization on the prepared powder and bulk materials and compare the results with the standard PDF card to determine the phases contained in the material and the corresponding crystal structure;
[0023] S3. By comparing the position heights of the three strongest diffraction peaks, explore the doping of materials and the orientation of the microstructure of bulk materials;
[0024] S4. Use field emission scanning electron microscopy to observe the morphology and microstructure of nanopowders, composite fractures, and polished surfaces of samples, use an energy spectrometer to observe element distribution, use secondary electron signals to obtain images, and use SEM to analyze the influence of microstructure on macroscopic properties;
[0025] S5. Use a transmission electron microscope to observe the microscopic morphology and grain boundary structure of the bulk sample after ion thinning, and use an energy spectrometer and selected electron diffraction to analyze special grain boundaries and observe the distribution of the second phase in the matrix;
[0026] S6. The Raman spectra obtained by confocal Raman microscope were used to analyze the defect changes of CNTs and GO by observing the characteristic peaks D and G of graphite and the D / G peak intensity ratio;
[0027] S7. Use electron backscatter diffraction to study the sample's orientation, the proportion of various grain boundaries, and the size and distribution of grains;
[0028] S8. Use an electron probe to characterize the distribution of the second phase. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] S9, Figure 1 It is a process diagram of the diamond anvil cell integrated technology electrode method in the present invention. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The present invention will be further described below in conjunction with the embodiments.
[0032] Example 1
[0033] A method for detecting the electrical transport properties of two-dimensional chalcogenide compounds under high pressure, comprising:
[0034] Step 1: Preparation of WS by solid phase reaction method 2-x Se2 polycrystalline samples, where X = 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1;
[0035] Among them, WS 2-x The steps for Se2 polycrystalline sample are:
[0036] 10) Follow 1 ∶ 1 ∶ 2 weight ratio weighing high purity W, Te, S e powder;
[0037] 11) Put the weighed high-purity W, S, and Se powders into a mortar, add alcohol and grind them, and heat at 55-85°C until the alcohol is completely evaporated;
[0038] 12) The uniformly mixed high-purity W, S, and Se powders are loaded into an Al2O3 crucible, and then placed into a quartz tube, and the quartz tube is evacuated and sealed using a vacuum tube sealing device;
[0039] 13) Place the sealed quartz tube into a box furnace, keep it at 650-750℃ for 12-14h, and then cool it down naturally to 20-25℃;
[0040] 14) Take out the sample, grind it again, press it into tablets, seal the tube, put it into a high-temperature chamber furnace at 750-850°C to sinter it into a phase, keep it warm for 12-14 hours, then naturally cool it down to 20-25°C and take it out.
[0041] Step 2: Prepare WS 2-x Se2 polycrystalline samples were sliced into rectangular thin slices.
[0042] Step 3: Measure the WS using the four-electrode method 2-x The resistivity variation curve of Se2 polycrystalline sample under zero field with temperature. The temperature T varies from 5K to 300K. The resistivity difference is calculated using the thermoelectric potential generated by the upper and lower electrodes. The protective gas is helium.
[0043] Step 4: Use the four-electrode method to test the WS at different temperatures T = 5K, 50K, 100K, 200K, and 300K. 2- x The resistivity of Se2 polycrystalline samples varies with the magnetic field, and the magnetic field range is 0 to 5T.
[0044] Step 5: Calculate the WS using the formula MR = [(ρ(H)-ρ(OT))] / ρ(H)×100% 2-x The magnetoresistance value of Se2 polycrystalline sample is obtained by 2-x The curve of magnetoresistance variation with magnetic field of Se2 polycrystalline sample.
[0045] In this embodiment, tellurium is a non-metallic element with a resistivity between that of metals and non-metals. It is a semiconductor material. Te element can not only form bonds with other elements or functional groups, but also can self-connect to form a negative divalent polymer anion group Sn. 2- (n=2-6), this type of anion group usually forms a bond with a metal cation or other organic cation and a transition metal amine complex cation group, so tellurides have a complex structure and rich physical and chemical properties, and have important application prospects in the fields of semiconductors, catalysis, photoconductors, nonlinear optics, etc. Using the solid phase reaction method, we explored WS 2-x Growth conditions of Se2 polycrystals, successful preparation of pure WS 2-x Se2 polycrystalline samples, study its magnetic transport properties, prepare WS 2-x Se2 polycrystal, its electrical transport properties are studied, WS 2-x The influence of temperature-resistance and magnetic field-resistance effects on Se2 polycrystals under high pressure provides a detailed reference experimental method for detecting the electrical transport properties of two-dimensional chalcogenides.
[0046] Example 2
[0047] A method for detecting the structure of a two-dimensional chalcogenide compound under high pressure comprises the following steps:
[0048] Step 1: Preparation of WS by solid phase reaction method 2-x Se2 polycrystalline powder and bulk samples.
[0049] Step 2: Perform XRD characterization on the prepared powder and bulk materials and compare the results with the standard PDF card to determine the phases contained in the material and the corresponding crystal structure. The XRD test conditions are: voltage 50-60kV, current 150-200mA, scanning speed 1-2° / min, and scanning degree 10-90°.
[0050] Step 3: By comparing the positions and heights of the three strongest diffraction peaks, explore the material doping and orientation of the bulk material microstructure.
[0051] Step 4: Use a field emission scanning electron microscope to observe the morphology and microstructure of nanopowders, composite material fractures, and sample polished surfaces, use an energy spectrometer to observe element distribution, use secondary electron signals to acquire images, and use SEM to analyze the influence of microstructure on macroscopic performance.
[0052] Step 5: Use a transmission electron microscope to observe the microscopic morphology and grain boundary structure of the bulk sample after ion thinning, and use an energy spectrometer and selected electron diffraction to analyze special grain boundaries and observe the distribution of the second phase in the matrix. Use an energy spectrometer and selected electron diffraction to analyze special grain boundaries and observe the distribution of the second phase in the matrix.
[0053] Step 6. Use the Raman spectrum obtained by confocal Raman microscope to analyze the defect changes of CNTs and GO by observing the characteristic peaks D and G of graphite and the D / G peak intensity ratio. The Raman spectrum test conditions are as follows: the laser wavelength is 510-530nm, the confocal diameter is 400μm, the slit width is 95-100μm, and the exposure time is 15-25s.
[0054] Step 7: Use electron backscatter diffraction to study the sample's orientation, the proportion of various grain boundaries, and the size and distribution of grains.
[0055] Step 8: The prepared powder and bulk materials are characterized by XRD detection technology, comparing the position and height of the three strong diffraction peaks, field emission scanning electron microscopy, transmission electron microscopy, electron backscatter diffraction and electron probe technology to determine the phases contained in the material and the corresponding crystal structure, and detect the prepared WS 2-x The characterization of the distribution of the second phase of Se2 polycrystalline samples provides a detailed reference experimental method for the detection of two-dimensional chalcogenide compound structures.
[0056] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for detecting the electrical transport properties of two-dimensional chalcogenide compounds under high pressure, characterized in that: include: S1. Preparation of WS by solid phase reaction method 2-x Se2 polycrystalline samples, where X = 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1; S2, prepare the WS 2-x Se2 polycrystalline samples were sliced into rectangular thin slices; S3, the WS is measured by the four-electrode method 2-x The resistivity curve of Se2 polycrystalline sample under zero field with temperature, the temperature T ranges from 5K to 300K; S4. The WS was tested at different temperatures of T = 5K, 50K, 100K, 200K, and 300K using the four-electrode method. 2-x The resistivity of Se2 polycrystalline samples varies with magnetic field, and the magnetic field range is 0 to 5 T; S5. Calculate the WS using the formula MR = [(ρ(H) - ρ(OT))] / ρ(H) × 100% 2-x The magnetoresistance value of Se2 polycrystalline sample is obtained by 2-x The curve of magnetoresistance of Se2 polycrystalline sample changing with magnetic field.
2. The method for detecting the electrical transport properties of two-dimensional chalcogenide compounds under high pressure according to claim 1, characterized in that: In step S1, WS is prepared 2-x The steps for Se2 polycrystalline sample are: S10, weighing high-purity W, Te, and Se powders in a weight ratio of 1:1:2; S11. Put the weighed high-purity W, Te, and Se powders into a mortar, add alcohol and grind, and heat at 55-85°C until the alcohol is completely evaporated; S12, loading the uniformly mixed high-purity W, Te, and Se powders into an Al2O3 crucible, and then placing the crucible into a quartz tube, and using a vacuum tube sealing device to evacuate and seal the quartz tube; S13, placing the sealed quartz tube into a box furnace, keeping it at 650-750°C for 12-14 hours, and then naturally cooling it down to 20-25°C; S14. Take out the sample, grind it again, press it into tablets, seal the tube, put it into a high-temperature chamber furnace and sinter it at 750-850°C. Keep it warm for 12-14 hours, then naturally cool it down to 20-25°C and take it out.
3. The method for detecting the electrical transport properties of two-dimensional chalcogenide compounds under high pressure according to claim 1, characterized in that: In steps S3 and S4, when the four-electrode method is used for detection, the resistivity difference is calculated using the temperature difference electromotive force generated by the upper and lower electrodes, and the protective gas is helium.
4. A method for detecting the structure of two-dimensional chalcogenide compounds under high pressure, characterized in that: The following steps are involved: S1. Preparation of WS by solid phase reaction method 2-x Se2 polycrystalline powder and bulk samples; S2. Perform XRD characterization on the prepared powder and bulk materials and compare the results with the standard PDF card to determine the phases contained in the material and the corresponding crystal structure; S3. By comparing the positions and heights of the three strongest diffraction peaks, explore the doping of materials and the orientation of the microstructure of bulk materials; S4. Use field emission scanning electron microscopy to observe the morphology and microstructure of nanopowders, composite fractures, and polished surfaces of samples, use an energy spectrometer to observe element distribution, use secondary electron signals to obtain images, and use SEM to analyze the influence of microstructure on macroscopic properties; S5. Use a transmission electron microscope to observe the microscopic morphology and grain boundary structure of the bulk sample after ion thinning, and use an energy spectrometer and selected electron diffraction to analyze special grain boundaries and observe the distribution of the second phase in the matrix; S6. The Raman spectra obtained by confocal Raman microscope were used to analyze the defect changes of CNTs and GO by observing the characteristic peaks D and G of graphite and the D / G peak intensity ratio; S7. Use electron backscatter diffraction to study the sample's orientation, the proportion of various grain boundaries, and the size and distribution of grains; S8. Use an electron probe to characterize the distribution of the second phase.
5. The method for detecting the structure of two-dimensional chalcogenide compounds under high pressure according to claim 4, characterized in that: In steps S2 and S3, the XRD test conditions are: voltage 50-60 kV, current 150-200 mA, scanning speed 1-2° / min, and scanning degree 10-90°.
6. The method for detecting the structure of two-dimensional chalcogenide compounds under high pressure according to claim 4, characterized in that: In step S5, the energy spectrometer and electron diffraction are used to analyze the special grain boundaries and observe the distribution of the second phase in the matrix.
7. The method for detecting the electrical transport properties and structure of two-dimensional chalcogenide compounds under high pressure according to claim 4, characterized in that: In step S6, the Raman spectrum test conditions are: the laser wavelength is 510-530 nm, the confocal diameter is 400 μm, the slit width is 95-100 μm, and the exposure time is 15-25 s.